2019
DOI: 10.1111/cns.13154
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effect of Fasudil on remyelination following cuprizone‐induced demyelination

Abstract: BackgroundMultiple sclerosis is characterized by demyelination/remyelination, neuroinflammation, and neurodegeneration. Cuprizone (CPZ)‐induced toxic demyelination is an experimental animal model commonly used to study demyelination and remyelination in the central nervous system. Fasudil is one of the most thoroughly studied Rho kinase inhibitors.MethodsFollowing CPZ exposure, the degree of demyelination in the brain of male C57BL/6 mice was assessed by Luxol fast blue, Black Gold II, myelin basic protein imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
2
4
0
Order By: Relevance
“…While, at a late stage of remyelination, all these outcomes improved as in the control group, except for rotarod performance and iNOS and IGF-1 levels, which remained unchanged. These results are consistent with previous findings (Chami et al, 2017 ; Wang J. et al, 2020 ; Yin et al, 2020 ) and confirm our study design, in which we examined our results at different time points during remyelination to avoid the effect of spontaneous remyelination by CPZ withdrawal on therapeutic intervention and to see whether the drugs can alter clinical symptoms shortly after disease onset, simulating treatment in humans. Overall, our results successfully established the CPZ-induced demyelination model in mice, and it is an excellent model for generating many essential features of MS disease and could be used to perform remyelination tests in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While, at a late stage of remyelination, all these outcomes improved as in the control group, except for rotarod performance and iNOS and IGF-1 levels, which remained unchanged. These results are consistent with previous findings (Chami et al, 2017 ; Wang J. et al, 2020 ; Yin et al, 2020 ) and confirm our study design, in which we examined our results at different time points during remyelination to avoid the effect of spontaneous remyelination by CPZ withdrawal on therapeutic intervention and to see whether the drugs can alter clinical symptoms shortly after disease onset, simulating treatment in humans. Overall, our results successfully established the CPZ-induced demyelination model in mice, and it is an excellent model for generating many essential features of MS disease and could be used to perform remyelination tests in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In several experimental studies, loss of body weight after CPZ intoxication was a surrogate indicator of the desired demyelination activity of CPZ in vivo (Hiremath et al, 1998 ; Yu et al, 2017 ). In our study, it was found that the body weight of the CPZ mice group was significantly decreased compared with the control group, which is in line with previous experimental studies indicating that the body weight of the CPZ mouse model of MS was significantly lower than that of the control mice (Omotoso et al, 2018 ; He et al, 2019 ; Mojaverrostami et al, 2020 ; Wang J. et al, 2020 ). Approximately 80% of patients with MS have deficits in motor functions, such as difficulty maintaining balance, decreased walking speed, and impaired dexterity of the hands and feet (LaRocca, 2011 ; Pellegrino et al, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…EAE and toxic demyelination induced by cuprizone (CPZ) are commonly used in animal models of MS that are used to study demyelination and remyelination during the infiltration of inflammatory cells in the CNS. Wang et al ( Wang et al, 2020 ) showed that fasudil could inhibit microglial-mediated neuroinflammation and promote astrocyte-derived nerve growth factor and ciliary neurotrophic factor in CPZ-induced demyelination. Arsenic trioxide is used to treat a variety of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The motor dysfunction of cuprizone-treated mice is usually subtle to observe as they appear normal, without obvious muscle weakness, paralysis, or any other visible physical signs as seen in the EAE model. However, by performing behavioral test such as beam-walking test, pole test, and rotarod test, it was demonstrated by others and our group that cuprizone-treated mice show affected locomotor-coordinative function [ 15 , 25 , 27 , 45 , 46 ]. In general, most studies [ 24 , 47 , 48 ] used 6- to 9-week-old mice maintaining a diet containing 0.2–0.3% cuprizone for 5-6 weeks to induce CNS demyelination.…”
Section: Discussionmentioning
confidence: 99%